Physics of electron emission from metal-dielectric cathodes; IEEE Transactions on Dielectrics and Electrical Insulation; Vol. 2, № 2 - Mesyats G. A. Gennady Andreyevich (1995, 1995)
В фонде НТБ ТПУ отсутствует